In vitro antimicrobial activity of Cassia tora L. stem - V.L. Deshmukh, R.T.Chavan, V.J. Kalane and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Ethanolic and aqueous extracts from the stem of Cassia tora were investigated for their antibacterial activity. Their concentrations 0.10mg, 0.25 mg ethanolic and aqueous extracts respectively were studied in activity, which involved the determination of inhibition zone in mm. Both the extracts exhibited significant antibacterial activity. Streptomycin used as standard reference. The antibacterial activity of ethanolic and aqueous extracts of Cassia tora has therefore been demonstrated for the first time.